Respostas

A melhor resposta!
2013-04-05T13:03:35-03:00

Sn = 72 
a1*a3 = 560 -> a3 = 560 / a1 

Sn = (a1 + a3)*n / 2 

(a1 + a3) = 2*Sn / n 

(a1 + 560 / a1) = 2*72 / 3 

a1² + 560 = 48*a1 

a1² - 48*a1 + 560 = 0 
coeficientes: 
a = 1 
b = - 48 
c = 560 

delta = b² - 4*a*c 
delta = (- 48)² - 4*1*560 
delta = 2304 - 2240 
delta = 64 

a1' = ( - b + raiz de delta) / 2*a = (+ 48 + 8) / 2*1 = 56 / 2 = 28 

a1'' = (- b - raiz de delta) / 2*a = (+ 48 - 8) / 2*1 = 40 / 2 = 20. 

---Verificação: 

a3 = 560 / a1 

a3 = 560 / 28 

a3 = 20 

---E também: 

a3 = 560 / a1 

a3 = 560 / 20 

a3 = 28 

---Esta deverá ser uma P.A. crescente, então fica: 

Sn = a1 + a2 + a3 

72 = 20 + a2 + 28 

a2 = 72 - 48 

a2 = 24. 

---A P.A. será: 

(20; 24; 28).

6 5 6